MASS MULTIPLICATION AND SELF LIFE OF TRICHODERMA SPECIES USING VARIOUS AGROPRODUCTS - SANTOSH KUMAR; PARTHA DEB ROY; MEHI LAL; GIREESH CHAND; VIVEK SINGH (The Bioscan, 2014)
Six agro based substrates such as sorghum grain, wheat grain, rice bran, rice husk, maize flour and saw dust were evaluated for mass production of three Trichoderma spp. Amongst, highest population was recorded in sorghum grain after 30 days of storage period of all three species i.e. T. harzianum (58.68 × 106 cfu/g) T. viride (54.24 × 106 cfu/g) and T. hamatum (52.51 × 106 cfu/g). The population of different species remained constant for a period of 60 days after which it started to decline slowly, the rate of decline varied with different substrates. The lowest population was observed in saw dust on T. harzianum (2.32 × 106 cfu/g). Sorghum based substrate could be useful for commercial production of Trichoderma spp with quality number of cfu which is essential for application of any bio- agent for management of plant diseases.